. Pengaruh Teh Hijau Pada Epigenetik dan Antiaging: The Effect of Green Tea on Epigenetics and AntiAging - Imelda Imelda; Hadyanto Lim (Universitas Methodist Indonesia, 2025)
Background: The global increase in aging population poses major public health challenges. Green tea, especially its bioactive compound epigallocatechin gallate (EGCG), has shown promising effects on healthspan and age-related diseases. Recent studies have explored its potential role in epigenetic regulation and antiaging mechanisms. Discussion: Green tea is rich in polyphenols, especially catechins like EGCG, which act as powerful antioxidants. EGCG modulates epigenetic mechanisms by inhibiting histone deacetylases (HDAC), altering DNA methylation, and regulating non-coding RNAs. These modifications support the expression of genes involved in cellular protection, stress resistance, and longevity. In addition to systemic benefits, green tea also demonstrates topical antiaging effects by reducing oxidative stress and improving collagen synthesis in the skin. Experimental models reveal EGCG’s capacity to delay aging through activation of key signaling pathways (e.g., AMPK, SIRT1, FOXO) and modulation of inflammatory and apoptotic mediators. Clinical studies further confirm that consistent green tea intake is associated with reduced epigenetic age and improved biological markers of aging Conclusion: Green tea, through its epigenetic influence and antioxidant properties, presents itself as a natural and effective antiaging agent. Regular consumption may contribute to the prevention of age- related diseases and the promotion of healthy aging.